The Impact of Companies' Internal Factors On The Performance of Their Stock Returns (Muhammadiyah University Press, 2019)
It is commonly known that in the capital market, not all stocks of companies that have a good profile will provide good returns to investors. Therefore, an in-depth analysis of the companies’ overall health is needed. This study aims to discuss the impact of companies’ internal factors on the performance of their stock returns. The companies meant here are those listed in the Jakarta Islamic Index (JII). The tool by which the data is analysed is panel data which is a combination of time series data and cross section. By employing companies’data of year 2014-2016, the study shows that Return On Assets (ROA), Net Profit Margin (NPM), Debt to Equity Ratio (DER) and Price to Book Value (PBV) simultaneously had a significant effect on the formation of stock returns of companies listed in the JII. Likewise, those four variables namely; ROA, NPM, DER and PBV partially have a significant effect on the formation of stock returns of companies listed in the JII.